The Implementation of Bio-Poems Strategy for Teaching Writing Descriptive Text of Person to Seventh Graders Students (RETAIN, 2017)
The Implementation of Bio-Poems Strategy for Teaching Writing Descriptive Text of Person to Seventh Graders Students David Wahyu Sapto Pamungkas1), Fahri2) 1) English Education student, Language and Art Faculty, State University of Surabaya, davidpamungkas@mhs.unesa.ac.id 2) English Education lecturer, Language and Arts Faculty, State University of Surabaya, fahri@unesa.ac.id Abstract English as a foreign language is a subject that should be learned by the students. In K13 Curriculum, students have to master 4 skill, those are listening, speaking, reading and writing. Writing is one of English skills which has to be mastered by the students. There are many materials in learning English Writing, one of them is descriptive text, especially descriptive text of person. The objectives of this study are to describe (1) The way of using bio-poems strategy in teaching and learning process. (2) The students’ writing descriptive text after the use of bio-poems strategy (3) the students’ responses toward learning descriptive text by using bio-poems strategy. This research was a descriptive research while the approach was qualitative technique. There were 3 instruments to conduct this research, those were observation checklist to know the teacher and students activities in class, students’ writing to know the students’ writing descriptive text after the use of this strategy, and questionnaire to know the students responses toward the use of this strategy in class. The result shows that “Bio-Poems’ strategy is appropriate to be implemented for teaching writing descriptive text of person to seventh graders students. It is proved from the observation result that the teacher and the students did the steps in right way. The activities in class were successfully done. Then based on the students’ writing descriptive text results, many students did the work great achievement, it proved from the result that most of students belong to “Good” criteria. Based on the questionnaire that was given in last meeting, most of the students were very excited when using this strategy in learning writing dscriptive text of person. Based on those result, it can be concluded that “Bio-Poems” strategy can be used for teaching writing descriptive text of person to seventh graders students. Keywords: English, descriptive text of person, Bio-poems strategy, literacy, strategy Abstrak Bahasa inggris sebagai bahasa asing merupakan salah satu mata pelajaran wajib di sekolah. Dalam kurikulum 2013, siswa wajib menguasai 4 kemamuan berbahasa inggris meliputi mendengar, berbicara, membaca dan menulis. Menulis merupakan salah satu keahlian berbahasa inggris yang harus dikuasai oleh siswa. Ada banyak materi dalam belajar menulis dalam Bahasa inggris, salah satunya adalah menulis teks deskriptif, khususnya teks deskriptif tentang orang. Penelitian ini bertujuan untuk mendeskripsikan (1) cara menggunakan strategi “bio-poems” dalam proses KBM. (2) hasil tulisan teks deskriptif siswa setelah penggunaan strategi “bio-poems”. (3) respon siswa terhadap pembelajaran menulis teks deskriptif tentang orang menggunakan strategi “bio-poems”. Penelitian ini merupakan penelitian deskriptif dengan menggunakan pendekatan teknik kualitatif. Ada 3 intrumen dalam pengadaan penelitian ini, meliputi pengamatan ceklis untuk mengetahui aktivitas-aktivtas guru dan murid dalam kelas, tulisan teks deskritif siswa guna mengetahui hasil tulisan teks deskriptif siswa setelah penggunaan strategi ini, dan kuisioner untuk mengetahui respon siswa terhadap penggunaan strategi ini dalam kelas. Hasil menunjukkan bahwa strategi “bio-poems” ini cocok untuk di terapkan dalam pengajaran menulis teks deskriptif tentang orang pada siswa kelas 7 smp, ini dibuktikan dari hasil pengamatan bahwa guru dan siswa melakukan langkah-langkah dengan tepat. Aktivitas-aktivitas dalam kelas terlaksana dengan baik. Lalu, berdasarkan hasil tulisan teks deskriptif siswa, banyak dari menyelesaikannya dengan baik, hal ini dibuktikan bahwa kebanyakan dari mereka tergolong berkemampuan “baik”. Berdasarkan kuisioner yang diberikan di pertemuan terakhir, kebanyakan siswa sangat senang ketika menggunakan strategy ini. Dapat disimpulkan bahwa strategi “Bio-poems” dapat digunakan untuk mengajar menulis teks deskriptif tentang orang pada siswa kelas tujuh. Kata kunci: Bahasa Inggris, teks deskritif tentang orang, strategi “bio-poems”.